O programa profuncionário e a valorização e profissionalização dos(as) servidores(as) não docentes da educação básica - Vargas, Cláudia Amélia (2015)
This study analyzed the educational public policies for the servers non-teachers of basic education, and the implementation of Profuncionário Program as training policy and professional development. Also diagnosed and measured the impact in general, the program has produced in educational institutions, and in particular posture changes of the graduates, and even if these professionals who participated in the program, in Goias, from 2006 to 2012, succeeded in becoming part of the learning process. It was a qualitative research, based on the dialectical materialism approach. As methodological procedures were adopted mainly for recording observations with the bibliographical research, documentary, with a questionnaire and interview. Although the theoretical grounding of the study was structured basically from the benchmarks of education and sociology, establishing also dialogue with scholars from other areas. The analysis and interpretation of the data collected revealed that professional non-teaching staff, after their inclusion in the process of training and professional development, they developed an educational professional identity. From the analysis, it was also possible, began to take a more active role in the daily educational institutions where they work, thus contributing to the effectiveness of a democratic management and a more active school community.